Comparative Study of Recovery after Sevoflurane versus Halothane Anaesthesia in Adult Patients - Ravi, PR (Med J Armed Forces India, 2008)
BACKGROUND: Induction and maintenance characteristics of sevoflurane and halothane have been studied, but little work has been done to compare the postoperative recovery of these two agents. METHODS: Sixty adult, ASA I and II patients were allocated randomly into Group A and Group B of 30 each. Group A received sevoflurane and Group B received halothane for maintenance. At the end of surgery early recovery, intermediate recovery and discharge criteria were assessed. RESULTS: Early recovery assessed with the mean time to extubation was 6.7 ± 2.29 min in Group A and 9.07 ± 1.64 min in Group B; eye opening was 7.28 ± 2.3 min in Group A and 10.6 ± 1.77 min in Group B; response to verbal command was 8.52 ± 2.83 min in Group A and 12.33 ± 2.17 min in Group B, while orientation was 10.43 ± 3.15 min in Group A and 14.77 ± 2.66 min in Group B. These differences were statistically significant (p<0.001). The mean time to reach post anaesthesia care unit discharge criteria was shorter for Group A (21.1 ± 4.69 min) as compared to Group B (27.43 ± 6.51 min) and this difference was statistically significant (p<0.001) CONCLUSION: Early recovery time and time taken to achieve discharge criteria were faster with sevoflurane.